2016
DOI: 10.2215/cjn.08110715
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Kidney Failure Risk Equation and Re-Calibration with Addition of Ultrasound Parameters

Abstract: Background and objectives Progression of CKD toward ESRD is heterogeneous. The Kidney Failure Risk Equation (KFRE) was developed to identify CKD patients at high risk of ESRD. We aimed to externally validate KFRE and to test whether the addition of predefined Duplex ultrasound markers -renal resistive index (RRI) or difference of resistive indices in spleen and kidney (DI-RISK) -improved ESRD prediction.Design, setting, participants, & measurements The prospective Cardiovascular and Renal Outcome in CKD 2-4 Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
(49 reference statements)
1
29
0
Order By: Relevance
“…Hence, 60% of US incident dialysis patients have only a catheter at initiation, while another 20% have a maturing AVF or AVG requiring a catheter at initiation. Furthermore, progression of chronic kidney disease (CKD) to ESRD requiring dialysis can be difficult to predict, 20, 21 thresholds for dialysis initiation vary, 22, 23 and patients may express reluctance toward access placement consistent with clinical expediency. 24 Timely vascular access planning and placement is thus fraught with multiple barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, 60% of US incident dialysis patients have only a catheter at initiation, while another 20% have a maturing AVF or AVG requiring a catheter at initiation. Furthermore, progression of chronic kidney disease (CKD) to ESRD requiring dialysis can be difficult to predict, 20, 21 thresholds for dialysis initiation vary, 22, 23 and patients may express reluctance toward access placement consistent with clinical expediency. 24 Timely vascular access planning and placement is thus fraught with multiple barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also showed that, during a median follow-up of 2.2 years, RRI ≥ 0.70 was significantly associated with increased all-cause mortality. 38 There is the notion that as RRI is highly influenced by extrarenal factors such as cardiac function and systemic arterial compliance, with pulse pressure being the principal determinant, its prognostic value has been related to vascular disease that is often systemic. Of note, those with RRI ≥ 0.70 had lower eGFR compared to those with RRI < 0.70, but this relationship with eGFR was not seen in the multivariate analysis.…”
Section: Rri and C Ard I Ova Scul Ar And Renal Outcome Smentioning
confidence: 99%
“…37 On the other hand, in a recent study, the routine Duplex examinations among stage 2-4 CKD patients did not improve risk prediction for progression to end-stage renal disease beyond a validated equation. 38 There is the notion that as RRI is highly influenced by extrarenal factors such as cardiac function and systemic arterial compliance, with pulse pressure being the principal determinant, its prognostic value has been related to vascular disease that is often systemic. 6 However, in a 7 years follow-up study of 726 Americans from the Cardiovascular Health Study Renal, Doppler signals from the renal parenchyma showed significant associations with subsequent CV events after controlling for other significant factors, such as renal function, HTN, diabetes and history of CV events.…”
Section: Rri and C Ard I Ova Scul Ar And Renal Outcome Smentioning
confidence: 99%
“…A PubMed search of prediction model yields over 40,000 papers. In CKD, research has focused on predicting CKD progression (1,2), cardiovascular events (3), and mortality (4-6) among many other outcomes (7). Interest in developing prediction models will continue to grow with the emerging focus on personalized medicine and the availability of large electronic databases of clinical information.…”
Section: Introductionmentioning
confidence: 99%